Intraorbital Trauma with Wooden Foreign Body: Report of An Atypical Surgical Case - Santos, Bárbara Sttephanny Silveira; Jesus , Oliver Renê Viana de; Arevalo , Andres Camilo Campo; Santos , Felipe José Menezes Machado; Kumar , Paulo Nand; Almeida Júnior , Paulo (Brazilian Journal of Implantology and Health Sciences, 2024)
Among the various types of injuries that affect the maxillofacial region, perforating objects can result in doubtful prognosis due to the possibility of reaching vessels, nerves, and other key structures, causing hemorrhages, airway obstruction, brain damage and even death. Foreign bodies in the orbital cavity are usually divided into two categories: inorganic and organic. This report intends to present an atypical case of wooden foreign body remotion from the intraorbital area which was performed surgically in a Public Hospital Center in Sergipe, Brazil. Facial injuries should be evaluated with a rigid protocol to provide quality healthcare, thus minimizing problems during the management of the cases. Imaging examinations should not be neglected, so that careful evaluation of the extent of the lesions and presence of foreign objects can be performed. Although CT is regarded as the gold standard, MRI scans are superior to CT in the diagnosis of small pieces of wood. Surgery is the preferred treatment, in which the surgeons should carefully remove all foreign bodies and residual fragments will result in orbital infection. Postoperative sinus drainage and systemic antibiotic treatments are necessary.